Diversity and the potency of indigenous bacteria in dengen fruit (Dillenia serrata), passion fruit (Passiflora edulis), and pineapple fruit (Ananas sp.) of South Sulawesi, Indonesia. Issue 1 (May 2021) - Tenriawaru, E P; Suharjono,; Ardyati, T; Zubaidah, E
Abstract: Fruit plays the important role in plant conservation, public health, and welfare. The fruit is used by society as foodstuff, drinks, and condiments. The objectives of this study were to analyze the nutritional content in some fruits originated in South Sulawesi (dengen fruit, passion fruit, and pineapple fruit), to observe the metagenomic diversity and the correlation among nutritional content and alpha diversity, the potency of indigenous bacteria contains in the fruits. These fruits have historical and commercial value. Furthermore, dengen and pineapple are endemic fruits and almost extinct. Ripe fruit samples were obtained from public plantations in Luwu Raya, South Sulawesi Province, Indonesia. The indigenous bacteria in some fruits were observed by prepare each fruit juice. Each fruit juice was filtered using filter paper followed by nitrocellulose membranes pore of 0.45 and 0.20 μm respectively. Each fruit juice measured for its acidity degree using a pH meter and the nutritional contents using the titration methods. The chromosomal DNA of bacterial cells had extracted by FastDNA Spin Kit (MPBIO), and partial of 16S rDNA amplified with 341f-806r primers, and it analyzed by Illumina platform. The sequence of 16S rDNA was analyzed by MUSCLE v.3.8.31, QIIME v.1.7.0, R v.2.15.3, and SPSS v.20 software. The results showed that pineapple fruit has the highest sugar, reducing sugar, starch, and amylose content, while dengen fruit has the highest vitamin C content. The combination of sugars and vitamin C content may influence the dominant microbial genera. Dengen fruit was dominated by Phylum Proteobacteria and it dominated by Genus of Acetobacter, Gluconobacter, and Komagataeibacter . Passion fruit and pineapple fruit were dominated by Phylum Firmicutes and Genus of Weissella . Genus of Acetobacter, Gluconobacter, and Komagataeibacter able to produce acetic acid, while Weissella is known as a lactic acid producer.